Perception and prejudice : race and politics in the United States - Hurwitz, Jon; Peffley, Mark (Yale University Press, 1998)
Based on one of the most extensive scientific surveys of race ever conducted, this book investigates the relationship between racial perceptions and policy choices in America. The contributors - leading scholars in the fields of public opinion, race relations, and political behavior - clarify and explore images of African-Americans that white Americans hold and the complex ways that racial stereotypes shape modern political debates about such issues as affirmative action, housing, welfare, and crime.